Students’ Difficulties in Solving AKM Numeracy Problems in Algebra: An Analysis Based on Learning Styles - Shafa Salsabila; Endang Cahya Mulyaning Asih; Dadan Dasari (Universitas Teknokrat Indonesia, 2025)
This study explores junior high school students’ numeracy skills in solving AKM-equivalent algebra problems based on their learning styles: visual, auditory, and kinesthetic. Using a qualitative case study design, nine students were selected through a learning style questionnaire and a numeracy test. Data were gathered using tests, interviews, and document analysis. The findings reveal that students with different learning styles demonstrate distinct strengths and challenges at each cognitive level (knowing, applying, and reasoning). High-proficiency students were able to solve problems across all levels, often using strategies aligned with their learning preferences. Moderate-proficiency students commonly faced difficulties in applying-level tasks due to conceptual misunderstandings, while low-proficiency students struggled across all levels, particularly with comprehension and focus. Despite these difficulties, students employed various successful strategies such as sketching, verbalizing, or imagining scenarios. The study highlights the importance of adaptive instruction that integrates learning style-based strategies. Practical recommendations are provided for educators to design inclusive numeracy instruction that enhances students’ mathematical understanding and problem-solving abilities.